Productive Contribution of Senior Citizens: Essential in promoting Family and Community Well-being - Radhika Kapur, (Indian Journal of Social Science and Literature (IJSSL), 2024)
In both urban and rural communities, throughout the country, there are senior citizens. They form the viewpoint that in old age, they aspire to get engaged in different types of tasks and activities, which would be facilitating in promoting well-being of family and community members. The tasks and activities are put into operation in personal and professional lives. For example, when in personal lives, the senior citizens are preparing favorite food items for their family members, they will incur the feelings of pleasure and contentment among them. On the other hand, in professional lives as well, they are engaged in different tasks and activities, which would be facilitating in promoting well-being and goodwill of community members. For example, in the education field, they still take classes and impart information in terms of academic subjects and lesson plans among individuals, hence, they are rendering a productive contribution. Furthermore, senior citizens impart information in terms of different types of subjects and concepts, which are facilitating in emerging into moral and ethical human beings and productive citizens of the country. Therefore, it is well-understood, productive contribution of senior citizens are essential in promoting family and community wellbeing. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of productive contribution, factors highlighting the productive contribution of senior citizens and measures to be implemented in augmenting productivity among senior citizens.